Study of single-mesh LC flashlamp driving circuit for xenon flashlamp - Maulud, Mohd. Fauzi; Mat Daud, Yaacob; Bidin, Noriah (Faculty of Science, University Teknologi Malaysia, 2008)

(untitled)
This paper is reporting the estimation of flashlamp driving circuits for xenon flashlamp as an optical pumping for solid-state laser. A linear xenon flashlamp with dimension 69 mm length and 4 mm bore diameter was employed. The circuit with combination capacitor and inductor used as pulse forming network (pfn) to control explosion energy given into the flashlamp. The determination of lc combination is important to transfer optimize energy between pfn and flashlamp. With flashlamp impedance 22 ohm amps0.5, storage capacitor energy of 50 joules and 58 µh inductor, a calculated value for peak current and discharge duration was determined. The peak current and discharge current were 635 amps and 227 µs respectively